The Challenge and Urgency of Gender Inclusion in Theological Education - Ortega Suárez, Ofelia (The ecumenical review, 2019)
Twenty years after the conclusion of the Ecumenical Decade of the Churches in Solidarity with Women, this article considers the development and the need for inclusion of gender in the sphere of theological reflection and education in Latin America and the Caribbean. Rather than a historical account, it proposes an approach that works toward thinking about and developing a new form of relationship between women and men, and between them and today's society and church.